After the gig how the sharing economy got hijacked and how to win it back - Schor, Juliet (University of California Press, 2020)
"When the "sharing economy" launched a decade ago, proponents claimed that it would transform the experience of work-giving earners flexibility, autonomy, and a decent income. It was touted as a cure for social isolation and rampant ecological degradation. But this novel form of gig work soon sprouted a dark side: exploited Uber drivers, neighborhoods ruined by Airbnb, racial discrimination, and rising carbon emissions. Several of the most prominent platforms are now faced with existential crises as they prioritize growth over fairness and long-term viability. Nevertheless, the basic model-a peer-to-peer structure augmented by digital tech-holds the potential to meet its original promises. Based on nearly a decade of pioneering research, After the Gig dives into what went wrong along the way to this contemporary reimagining of labor. The book examines multiple types of data from thirteen cases to identify the unique features and potential of sharing platforms that prior research has failed to identify. Juliet B. Schor presents a compelling case that we can engineer a reboot: through regulatory reforms and cooperative platforms owned and controlled by users, an equitable and actual sharing economy is still possible"--